A Map Is More Than Just a Graph: Geospatial Educational Research and the Importance of Historical Context - Matthew Gardner Kelly (AERA Open, 2019)
In this article, I discuss the promise of geospatial techniques for education policy research and how increased attention to the historical context of spatial data can enhance that work. While scholarship utilizing geographic information systems has added considerable breadth to our understanding of education policy, recent geospatial studies in education policy tended to neglect long-term, historical trends. Drawing on research in geography dealing with temporality, this article discusses the critical importance of historical context for spatial analysis. Then, to illustrate this point, I use the example of education policy research on school district boundaries to suggest the benefits of extending our temporal frame when conducting geospatial educational research. Greater attention to the historical context of geospatial data can (1) help policy researchers generate new research questions, (2) enhance their use of quantitative spatial analysis techniques, and (3) deepen their understanding of the underlying causes of contemporary patterns in the distribution of educational opportunity.